Poultry litter management in Lagos and effects of its soil application on the growth of okra (Abelmoschus esculentus (2015)
Poultry litter constitutes one of the animal wastes that are produced in large quantity. Information on the quantity generated may enhance planning for its utilisation. Quantification of poultry litter (PL) generated and its utilisation is rare in Nigeria. This study was designed to investigate PL management in Lagos, Nigeria and possible utilisation potential. Questionnaires were distributed to poultry farmers in Lagos to evaluate poultry waste generation and management practices. Additionally, PL was also quantified from selected farms. Greenhouse experiments were conducted to evaluate the agronomic effects of raw and composted PL (each applied at 0, 5, 10 t/ha and replicated four times) on the growth and heavy metals uptake of Abelmoschus esculentus (okra). Poultry farms were situated in the residential, non-residential and industrial areas with non-residential areas housing a larger percentage. About 53% of the farms were located near rivers or streams. A few of the poultry farmers treated and utilised PL using chemical and physical methods before disposal. Also, no record of waste utilization was found in 72.3% of the farms. About 87.4% of the farmers quantified the PL generated. About 89.3% of the farmers disposed PL in open dumpsites. Mean poultry litter generated from four farms per bird/day was 0.11 ± 0.001 kg. The HMs contents in plants grown on the poultry treated soils were below the permissible levels in soil. The heavy metals concentrations in the leaves and fruits (which are usually the edible parts of okra plants) for all the treatments fall within WHO/FAO permissible levels. Overall, soil amended with 5 t/ha composted poultry litter performed best in terms of fruit production and reduction in HMs uptake. The use of composted poultry litter as fertiliser at calculated quantity will increase PL management.